Utility-optimal random access for wireless multimedia networks - Cheung, Man Hon; Mohsenian-Rad, Hamed; Wong, Vincent W. S.; Schober, Robert (IEEE Wireless Communications Letters, 2012)
In this letter, we consider the uplink random access problem in a wireless multimedia network (WMN) with audio, video, and best effort applications. Since these multimedia applications have different quality-of-service (QoS) requirements, we model their utilities with concave, step, and quasi-concave functions. We assume that the access point performs admission control and assigns transmission probabilities to the users for random access, based on solving a non-convex network utility maximization problem. We propose a novel enumeration algorithm to obtain the global optimal solution by solving a number of computationally tractable convex optimization problems. We characterize the total number of iterations of the algorithm analytically. Simulation results show that our proposed algorithm achieves a higher average network aggregate utility than a carrier sense multiple access (CSMA) scheme implemented in a slotted time system. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Random access; wireless multimedia networks